Ans :15
X be a present age of mudit
After 18 year age of mudit is X+18
4 year ago age was X-4
As per question,
X+18=3(X-4)
X+18=3X-12
3X-X=18+12
2X=30
X=15
Ans :15
X be a present age of mudit
After 18 year age of mudit is X+18
4 year ago age was X-4
As per question,
X+18=3(X-4)
X+18=3X-12
3X-X=18+12
2X=30
X=15
Ans :15
X be a present age of mudit
After 18 year age of mudit is X+18
4 year ago age was X-4
As per question,
X+18=3(X-4)
X+18=3X-12
3X-X=18+12
2X=30
X=15
Ans :15
X be a present age of mudit
After 18 year age of mudit is X+18
4 year ago age was X-4
As per question,
X+18=3(X-4)
X+18=3X-12
3X-X=18+12
2X=30
X=15